Challenges and policy lessons for the growth-employment-poverty nexus in developing countries - Gary S. Fields (IZA Journal of Labor Policy, 2012)
Of the world's 6.7 billion people (as of 2008), 1.3 billion lived on less than 1.25 Purchasing Power Parity dollars per person per day and another 1.7 billion lived on between 1.25 and 2.50 PPP dollars (Chen and Ravallion, 2012). The scourge of absolute economic misery among billions of the world's people is one of the most serious problems facing humankind today. Unemployment (defined below) befalls about 200 million of the world's people - a sizeable number but small compared to the three billion people who are poor using the 2.50 PPP dollar poverty line. A much larger number - 900 million - are employed but earning so little that they and their families are unable to reach even 2 per person per day (ILO, 2012). They are working hard and they are working poor. (Working Hard, Working Poor is the title of my latest book (Fields, 2012). To achieve more and better employment (where 'better' depends on such factors as rate of pay, job security, employment protections, and type of work), analysts and donors need to understand better how employment, growth, poverty and other factors interact, how unemployment is caused, and how employment can be improved. At the same time, drawing on practical experience, research can identify knowledge gaps that to date pose limits to successful employment creation policy.
Keywords: I3; O1; O19; J2; 330; employment; poverty; economic growth; foreign assistance; developing countries; Erwerbstätigkeit; Wirtschaftswachstum; Armut; Entwicklungshilfe; Entwicklungsländer